The Effect of Pregnancy Gymnastics on Reducing Pain on The Backs of Pregnant Women in the Practice of Independent Midwives Sri Ratu Alam Batam City in 2022 - Lisa Putri Utami Damanik; Sri Ratu Alam (Institute of Computer Science (IOCS), 2022)
Pregnancy brings great changes in the female body, including the back. Since entering the second tricemester period, some pregnant women began to experience back pain due to the increasingly large baby. 50-80% of women have experienced back and hip pain during pregnancy, chiropractic doctor Ronald J. Tyszkowski said. Back pain is a side effect of a normal pregnancy. The prevalence of spinal pain in pregnant women occurs more than 50% in the United States, Canada, Iceland, Turkey, Korea, and Israel. Meanwhile, in northern America, Africa, the Middle East, Norway, Hong Kong, the prevalence is higher which ranges from 21% to 89.9%. The results of research on pregnant women in various regions in Indonesia reached 60-80% of pregnant women experiencing back pain in their pregnancies. In East Java, around 65% of all pregnant women experience back pain. The method used with the Crossectiona design was a study sample of pregnant women in the II and III trimesters with a total of 35 people. Based on the results of research conducted at BPM Sri Ratu Alam Batam City on, using the Statistics Produck Service Solution (SPSS) program and from the analysis using the Chi-Square test, a P Value value = 0.001 < 0.05 was obtained, this shows that there is an influence of pregnant gymnastics on reducing pain in the back of pregnant women at BPM Sri Ratu Alam Batam City